The six Marine divisions in the Pacific every campaign of World War II - Clark, George B. (McFarland, 2006)
"Concentrating on the infantry units, this volume provides a brief history of each of the six Marine divisions which took part in the Pacific conflict. Beginning with a chronology of the war, it describes each campaign through the eyes of a specified division, focusing on the division's exact movements and actions. Maps and photographs are also included"--Provided by publisher.
"Concentrating on the infantry units, this volume provides a brief history of each of the six Marine divisions which took part in the Pacific conflict. Beginning with a chronology of the war, it describes each campaign through the eyes of a specified division, focusing on the division's exact movements and actions. Maps and photographs are also included" - Provided by publisher.
Includes bibliographical references and index
Keywords: United States -- Marine Corps -- History -- World War, 1939-1945; United States -- Marine Corps -- Organization; USA -- Marine Corps; Geschichte; Weltkrieg (1939-1945); World War, 1939-1945 -- Campaigns -- Pacific Area; Pazifikkrieg -- 1941-1945; Organisation; Pazifischer Raum; USA